Analyzing the Views of Religion in the Individualism of Moralism Between Religions - Muhammad Fauzan Azhima; Idris Siregar (Values: Jurnal Kajian Islam Multidisiplin, 2024)
Moralism is a global phenomenon that can be found in various societies that adhere to "world religions" such as Judaism, Hinduism, Christianity and Islam. The purpose of this research is to know that the faith of religion is entirely based on their individual and personal achievement, and given by the pride given to the personal experience that guides everyone in their own way. Religion is a basic human necessity, because religion is a means of defending itself against all acts of violence that threaten human life. Religion gives meaning to individual life and also gives hope for survival after death. Religion can be a human tool to rise from the world's life of suffering, to achieve spiritual independence. Religion as a symbol of society is no longer visible since religion has been established as religious institutions, institutional religions in principle create a good institutional regime based on faith validation, using a secure president according to the authoritarian organisation that conforms to each tradition, in connection with the line of religious descent. Religion has become a legitimate tool for a group of people who have economic and political resources.